Pseudomastax graciollii sp. nov., a new monkey-grasshopper species from the Amazon and comments on other species of the genus (Orthoptera: Eumastacidae: Pseudomastacinae) - Olivier, Renan Da Silva (Zootaxa, 2018)
Pseudomastacinae is a monogeneric subfamily with 22 valid species, distributed among five South American countries. Species of Pseudomastax are very similar morphologically and especially in respect of their coloration, which is typically black with white/yellow detail in males and brown in females. The most evident differences are in male cerci and phallic complex, structures typically used in the taxonomy of the group. Herein is described a new species for the genus, Pseudomastax graciollii sp. nov. In addition, the female of P. personata is redescribed and new records are presented for this species and P. nigroplagiata.